On Light Mapping and Certain Concepts by Using m_X N-Open Sets - haider jebur Ali (Baghdad Science Journal, 2020)
The aim of this paper is to present a weak form of -light functions by using -open set which is -light function, and to offer new concepts of disconnected spaces and totally disconnected spaces. The relation between them have been studied. Also, a new form of -totally disconnected and inversely -totally disconnected function have been defined, some examples and facts was submitted.